(untitled) (Experimental biology, 2019)
On this article describes method determination of sodium and potassium in fruit of medicinal plants family Elaeagnаceae by atomic absorption spectrometry. According to their content in living organisms, potassium and sodium are indispensable macronutrient, they are actively involved in metabolism, therefore these elements were identified from the species medicinal plants of the family Elaeagnаceae. As the objects of the study we collected three populations of the family Elaeagnaceae, they are Hippophae rhamnoides and Elaeagnus oxycarpa, they were collected in the Almaty region, Karasai district and Khengen district. During the experiment was performed the calibration schedule by comparing the elements of study in the fruit of family Elaeagnаceae with a standard solution. Usually prepared three comparative solutions and experimental solution, but during the reaserch work were prepared six solutions. Standard solutions of potassium and sodium (100 μg / ml) were prepared by mixing with ionized water accordıng to GSO 7474-98. In accordance with the results, a high concentration was determined from the fruits of the species Elaeagnaceae family. The World Health Organization pays great attention to drugs derived from medicinal plants. Therefore, nowadays it is important to study the healing properties of medicinal plants. From the fruits of the species belonging to the family Elaeagnаceae, as a valuable medicinal raw material for traditional and national medicine was demonstrated methods of use for various purposes and rules for collection. Key words: Elaeаgnаceae, Hippophaе rhamnoides, Elaeagnus oxycarpa, medicinal plants.